Educational Aspects Of The Environment Around As A Learning Source For The Mastery Of Ips Concept In Class V Sd Negeri 16 Pulau Karam Kecamatan Koto Xi Tarusan - Darmis Darmis (Fakultas Sastra Universitas Ekasakti, 2018)
IPS research has been conducted to Improve IPS Learning Achievement Through As Learning Sources For Mastery of IPS Concept For Grade V Students of SD Negeri 16 Pulau Karam Kecamatan Koto XI Tarusan. The purpose of this study is to determine the quality of IPS education by utilizing the surrounding environment as a source of learning. To know the influence of application of Learning Model with Environmental Approach to student learning outcomes in primary school. To know the students' perceptions of the implementation of learning by utilizing the surrounding environment as a source of learning. To identify the factors that become obstacles in implementing Learning Model with Environmental Approach. This type of research is a classroom action research (PTK). Instrument used to measure IPS Learning Achievement Through As a Learning Source for Mastery of IPS Concept. This research consist of 2 cycles, in 1 cycle consist of 1 meeting, meeting process on cycle I and cycle II students are given contextual problem. Before the action is done first conducted interviews with teachers in the field of IPS studies to determine the initial ability and early difficulties of students. From the interview results obtained information that students have not studied the material, thus before the study is given initial knowledge of students about the material. After giving action I the level of student's learning achievement is 48.57% classical, in this case there are only 10 students who have completed in learning achievement with average achievement of class 60,8 including in medium category. Furthermore, after the implementation of action II, the level of students' achievement in classical mathematics is 42.86%, in this case there are only 10 students who have completed in IPS learning achievement with average achievement of 58.94 class included in low category. From this there is a decrease in classical mastery level of 5.71% for IPS learning achievement. Based on the results of this study obtained that realistic IPS learning can not Improve IPS Learning Achievement Through As a Learning Sources For Mastery Concept IPS For Students Class V SD Negeri 16 Pulau Karam Sub Koto XI Tarusan.